2004
DOI: 10.1007/s12019-004-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

Severe health anxiety: Why it persists and how to treat it

Abstract: Hypochondriasis (HA) involves the fear of serious illness despite appropriate reassurances. Because HA is associated with patients' personal suffering and clinical management problems, it is important for clinicians to be knowledgeable about current conceptual and treatment approaches to this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
1
0
3
Order By: Relevance
“…In both studies, only a few percent of participants with baseline pain reported no pain at follow-up. Likewise, health related concerns, such as health anxiety, are also considered a persistent trait despite reassurance [ 66 , 67 ]. However, data quality would have been increased had we had repeated measures over time of pain sites.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, only a few percent of participants with baseline pain reported no pain at follow-up. Likewise, health related concerns, such as health anxiety, are also considered a persistent trait despite reassurance [ 66 , 67 ]. However, data quality would have been increased had we had repeated measures over time of pain sites.…”
Section: Discussionmentioning
confidence: 99%
“…Abramowitz ve ark. ( 2004) tarafından obsesyon, panik gibi ruhsal hastalığı olan bireylerle yapılan çalışmada sağlık anksiyete puan ortalaması 36.60±13.20 olarak tespit edilmiştir (Abramowitz & Deacon, 2004). Ülkemizde ise Yılmaz ve Dirik (2020) tarafından sağlıklı bireyler üzerinde yapılan çalışmada sağlık anksiyetesi puan ortalaması 16.69±7.61 olarak düşük düzeyde tespit edilmiştir (Yılmaz & Dirik, 2020).…”
Section: Discussionunclassified
“…Bulgularımız sağlıklı bireylerdeki yapılan çalışmalarla benzerlik göstermektedir. Sağlık anksiyetesi yaşayan bireylerin vücutlarında meydana gelen değişimlere daha duyarlı olduğu ve daha fazla sağlığı koruyucu eylemde bulunduğuna işaret edilmektedir (Abramowitz & Deacon, 2004). Ancak Jones ve ark.nın (2020) gerçekleştirdikleri çalışma, sağlık anksiyetesi olan bireylerin sağlık hizmetleri almaktan kaçınabileceğini göstermiştir (Jones ve ark., 2020)…”
Section: Discussionunclassified
See 1 more Smart Citation